What makes a Grand Slam champion? Early engagement, late specialization and timely transition from having fun to dedication - Oršolic, M.; Barbaros, P.; Novak, D. (Frontiers in Sports and Active Living, 2023)
In order to provide adequate support for young tennis players, it is important to understand the development path and factors which can have a positive or negative impact on the development of a player. The aim of this research was to determine the factors that affected sports specialization in tennis by means of qualitative analysis (early, optimal, or late). As well as to deepen the knowledge around the phenomenon of specialization in tennis among players of differing success levels through their personal experiences, in order to contribute to a better understanding of their specialization. The authors interviewed 30 tennis players of differing levels, including 10 participants from the most elite level (Grand Slam champions), exploring their contrasting experiences of development. The data set was analyzed using reflexive thematic analysis. Three topics were generated, which included the following: engaging in sport, decisions, and time of specialization. The obtained results offer a stimulus to reflect on numerous aspects of athlete development.